Rancang Bangun Sistem Informasi Penjualan Cat Pada PT. Handal Cahaya Sakti - Cahyadi, Jeffry; Tjandrarini, Asteria; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2015)
Jotun is one of the most outstanding producers paint in the world. PT. Handal Cahaya Sakti (HCS) is one of the Jotun dealers, which distributes ship paint in Indonesia. Actually PT. HCS has four main problems. Firstly, there is no accurately inventory information. Secondly, the process of data search needs long time. Thirdly, the accounting process of paint selling price still uses calculator. Lastly, the stored data that is not computerized and managed will be the useful information for the company. Based on those problems, the sales information system design hoped can improve the performance and decrease the error. The computerized data will be easier to be back-up, searched and managed.